Pengaruh Disiplin Kerja, Loyalitas, Lingkungan Kerja dan Pengembangan Karir Terhadap Kinerja Karyawan Pada PT. Socfindo Aek Pamienke Kabupaten Labuhanbatu Utara - Sihombing, Widya Fransiska; Nasution, Ade Parlaungan; Prayoga, Yudi (Universitas Labuhanbatu, 2021)
This study aims to determine the influence of work discipline, loyalty, work environment and Career Development on employee performance at PT. Socfindo AEK Pamienke North Batu Labuhan Regency. This Type Of Research Is Associative Research. Data collection in this study was conducted through a survey approach with a type of quantitative descriptive research by distributing questionnaires to 50 respondents, while the population used in this study are employees in the factory division precisely in the field of factory operators. Data collection techniques are carried out by interviews, questionnaires and documentation studies.Data analysis tools used in this study using SPSS (Statistical product Sofware Solution).Data analysis techniques in this study are descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significant Test (t test), simultaneous significant test (F test), and determination coefficient test (R2).The results showed simultaneously variable work discipline, loyalty, work environment and Career Development significant effect on employee performance positive and significant effect on employee performance Fhitung 41,479> Ftabel2. 58 with a significant value of 0,000 < 0,05,partially work discipline positive and significant effect on employee performance obtained value thitung 2,776> ttabel1, 679 and the probability value of t is 0,008< 0,05,partially loyalty positive and significant effect on employee performance obtained value thitung4, 915> ttabel1,679 and the probability value of T is 0.000 < 0.05, work environment positive and significant effect on the performance of employees obtained value thitung 2.547 > ttabel1, 679 and the probability value of t is 0.014 < 0.05. Career development positive and significant effect on employee performance obtained value thitung 2,612 > ttabel1, 679 and the probability value of T is 0,012< 0,05 magnitude value R Square 0,787 or equal to 78,7%. Version 22.